Determining residents’ enjoyment of Cantonese opera as their performing arts heritage in Macao - Man-U, Lo; Chong, Daniel Ka Leong * (Taylor & Francis, 2020)
This study attempts to empirically investigate Macao residents’ perception and enjoyment of their traditional performing arts - Cantonese opera. By examining the relationship between the experiential attributes and intrinsic artistic components of Cantonese opera, this study found that the experiential attributes and intrinsic craftsmanship were significantly correlate and influence on the residents’ enjoyment of their traditional performing arts. While the constructs of “identity connection” and “leisure experiential benefits” are found to have significant prediction towards the intrinsic craftsmanship and residents’ enjoyment of Cantonese opera, the intrinsic craftsmanship is the strongest latent variable to predict residents’ enjoyment. Moreover, the statistical results reveal that Macao residents’ consumption experience of Cantonese opera vary with their socio-demographic characteristics, particularly the residents’ birthplace and age. This study empirically supports that the experiential attributes associated with tangible cultural heritage can apply to intangible cultural heritage and influence its attractiveness. Some practical and theoretical implications are suggested.